A comprehensive evaluation of organic micropollutants (OMPs) pollution and prioritization in equatorial lakes from mainland Tanzania, East Africa. (15th June 2022) - Zhao, Zhonghua; Yao, Xiaolong; Ding, Qiqi; Gong, Xionghu; Wang, Jianjun; Tahir, Saadu; Kimirei, Ishmael Aaron; Zhang, Lu
Highlights: Occurrence of 70 organic micropollutants (OMPs) in water and sediment of Tanzanian lakes were investigated. Phthalates (PAEs) were the dominant OMP in both water and sediment, followed by polycyclic aromatic hydrocarbons (PAHs). Thirty-one chemicals were screened as high priority in water while thirty-three in sediment. The final OMP priority list for Tanzanian lakes was composed of 25 chemicals with DEHP being dominant. Abstract: A lack of understanding the fate of highly toxic organic micropollutants (OMPs) in the equatorial lakes of Tanzania hinders public awareness for protecting these unique aquatic ecosystems, which are precious water resources and stunning wildlife habitats. To address this knowledge gap, the occurrence of 70 anthropogenically-sourced OMPs, including phthalates (PAEs), polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs), was investigated in the water and sediment of 18 lakes in Tanzania. Similar residue concentrations were found in both compartments, showing higher pollution of PAEs ranging from 835.0 to 13, 153.1 ng/L in water and 244.6–8691.8 ng/g dw in sediment, followed by PAHs, while OCPs and PCBs were comparatively lower. According to the multi-criteria scoring method for prioritization, the final OMP priority list for the lake environment in Tanzania comprised 25 chemicals, specifically 5 PAEs (DEHP, DIBP, DBP, DCHP and DMPP), 6 PCBs (PCB153, PCB105, PCB28, PCB156, PCB157 and PCB167), 6 PAHs (BaP, BaA, BbF, Pyr, DahA and InP) and 8 OCPs (cis-chlordane, trans-chlordane, p, p '-DDD, p, p '-DDE, p, p '-DDT, endrin, methoxychlor and heptachlor epoxide), suggesting the key substances for conventional monitoring and pollution control in these equatorial lakes, with an emphasis on PAEs, especially DEHP, due to the top priority and endocrine disruptor properties. Graphical abstract: Image, graphical abstract